A nanofiber air filter membrane and its preparation method and application

By using water as a solvent and electrospinning technology, a degradable nanofiber air filter membrane was prepared, which solved the problems of organic solvent emissions and environmental pollution in the production process of electrospinned nanofiber materials, and achieved efficient air filtration and environmental friendliness solution.

CN118949717BActive Publication Date: 2024-12-20SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411449537.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-20
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing electrospun nanofiber air filter materials emit a large amount of organic solvents during the production process, which poses safety risks, and the nanofiber materials cannot degrade, resulting in environmental pollution.

Method used

Using water as the only solvent, polymers, nanoparticles and acidic solutions that can ionize hydroxyl groups by hydrolysis, combined with electrospinning technology to prepare nanofiber air filter membranes, avoiding the use of organic solvents, and through specific chemical composition and treatment methods Making nanofibers degradable in soil.

Benefits of technology

It has achieved improvements in environmental and air safety, reducing safety risks in the preparation process. The nanofiber air filter membrane can naturally degrade within 6 to 10 days, with a degradation rate of more than 99%, and has good moisture resistance and long-term Lifespan, while improving air filtration efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118949717B_ABST
    Figure CN118949717B_ABST
Patent Text Reader

Abstract

The present application relates to the field of gas purification technology, and provides a nanofiber air filter membrane and a preparation method and application thereof. The nanofiber air filter membrane is made of the following raw materials: a polymer that can be hydrolyzed to ionize hydroxyl groups, an organic matter, nanoparticles, a solvent, and an acidic solution; wherein the mass ratio of the polymer that can be hydrolyzed to ionize hydroxyl groups, the solvent, the organic matter, and the nanoparticles is 0.8-1.2: 8-12: 0.2-0.6: 0.004-0.012, and the pH value of the acidic solution and the solvent after mixing is 4.5-6. The nanofiber air filter membrane can be naturally degraded in the soil within 6-10 days, and the degradation rate is greater than 99%. The nanofiber air filter membrane no longer dissolves in water, has good moisture resistance, and therefore has a good service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of gas purification technology, and in particular relates to a nanofiber air filtration membrane and a preparation method and application thereof. Background Art

[0002] The content of fine particles in the air (such as PM2.5) is very small in the atmosphere, but due to its small size and slow settling speed in the air, it seriously reduces the visibility of the air and has an unprecedented adverse impact on the physical chemistry of the atmosphere, the biosphere and the climate. Moreover, these suspended particles and the pollen, bacteria, fungi, viruses, etc. adsorbed on their surfaces are easily inhaled into the human body, which can cause or aggravate respiratory, cardiovascular, infectious and allergic diseases.

[0003] Most of the air filter materials currently used are made of meltblown nonwoven fabrics, but they have low efficiency and high resistance. Electrospun nanofiber air filter materials came into being. They not only save the energy consumption of heating and hydrolyzing polymers that can ionize hydroxyl groups during the preparation process, but also have low resistance during use. The reason why electrospun filter materials have low resistance is that their fiber diameter is fine, the specific surface area is large, the porosity is high, the pore size is small, and they have some special physical and chemical properties. Only a very thin layer of nanofiber air filter membrane (2-3 layers of nanofiber layers) can achieve a very high filtration efficiency (higher than 99%).

[0004] However, the current problem with electrospun nanofiber air filtration materials is that a large amount of organic solvents are emitted during the production of the nanofibers, which can easily pollute the air and pose a safety hazard. In addition, the nanofiber materials cannot be degraded and can easily pollute the environment after being discarded. Summary of the invention

[0005] The purpose of this application is to provide a nanofiber air filtration membrane and its preparation method and application, aiming to solve the pollution and safety problems existing in the current production process of electrospun nanofiber air filtration materials and the environmental problems caused by the inability to degrade itself.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present invention provides a nanofiber air filtration membrane made of the following raw materials;

[0008] Hydrolyze polymers, organic matter, nanoparticles, solvents and acidic solutions that can ionize hydroxyl groups;

[0009] The mass ratio of the polymer that can ionize hydroxyl groups by hydrolysis, the solvent, the organic matter and the nanoparticles is 0.8-1.2:8-12:0.2-0.6:0.004-0.012, and the pH value of the acidic solution and the solvent after mixing is 4.5-6;

[0010] Wherein, the organic matter is melamine, silicon tetrachloride or divinylbenzene;

[0011] The nanoparticles are at least one of aluminum oxide, zirconium dioxide and silicon dioxide.

[0012] As a possible design, the polymer that can ionize hydroxyl groups upon hydrolysis is at least one of polyvinyl alcohol, polyacrylamide, polyacrylic acid, polyvinyl pyrrolidone, polymaleic anhydride and polyethylene glycol.

[0013] As a possible design, the particle size of the nanoparticles is 10-500 nm, preferably 10-100 nm.

[0014] As a possible design, the mass ratio of the polymer that can ionize hydroxyl groups by hydrolysis, the solvent, the organic matter and the nanoparticles is 1:10:0.5:0.01, and the pH value of the acidic solution and the solvent after mixing is 5.

[0015] In a second aspect, the present invention provides a method for preparing a nanofiber air filtration membrane, comprising the following steps:

[0016] The polymer capable of ionizing hydroxyl groups by hydrolysis is dissolved in a part of the solvent to form a viscous liquid A, wherein the concentration of the viscous liquid A is 5-20 g / mL;

[0017] Melamine, silicon tetrachloride or divinylbenzene are dissolved in part of water to form a uniform solution, and then an acidic liquid is added for cross-linking to form a viscous liquid B, wherein the concentration of the viscous liquid B is 10-30 g / mL;

[0018] adding the nanoparticles into the remaining solvent and dispersing them to form a suspension solution C;

[0019] The suspension solution C is added dropwise to the viscous liquid B, and the mixture is stirred at room temperature to obtain a viscous liquid D;

[0020] Viscous liquid D is added to viscous liquid A and stirred to form a mixed solution E;

[0021] The mixed solution E is spun to obtain a primary nanofiber air filter membrane;

[0022] The newly formed nanofiber air filter membrane is dried and dehydrated to obtain the nanofiber air filter membrane.

[0023] As a possible design, the temperature for adding the acidic liquid for cross-linking is 70-90°C and the time is 30-48 hours; preferably, the temperature for adding the acidic liquid for cross-linking is 75-82°C and the time is 34-40 hours.

[0024] As a possible design, the spinning adopts an electrostatic spinning method or an airflow spinning method. The spinning conditions of the electrostatic spinning are: a voltage of 10~25kV, a collection distance of 5~100 cm, a liquid feed speed of 0.1~100 mL / h, and an airflow speed of 0.1~50m / s; the conditions of the airflow spinning method are: a collection distance of 5~100 cm, a liquid feed speed of 0.1~100 mL / h, and an airflow speed of 0.1~50m / s.

[0025] As a possible design, the collection distance is 5~50 cm, the liquid inlet rate is 0.1~10 mL / h, and the air flow rate is 0.1~20 m / s.

[0026] As a possible design, the acidic liquid includes at least one of hydrochloric acid, nitric acid and acetic acid.

[0027] The beneficial effects of the present invention are:

[0028] 1. The nanofiber air filter membrane disclosed in the present invention uses only water as a solvent in the entire preparation process without involving any organic solvents, so it is good for the environment and air, and reduces the safety hazards in the preparation process.

[0029] 2. Nanofiber air filter membrane can be naturally degraded in the soil within 6 to 10 days, with a degradation rate of more than 99%.

[0030] 3. The nanofiber air filter membrane no longer dissolves in water and has good moisture resistance, so it has a good service life.

[0031] 4. The preparation method of the present invention is simple and easy to implement and can be widely promoted and applied.

[0032] 5. The nanofiber air filter membrane prepared by the present invention can not only be used for air filtration, but also for purification of industrial exhaust gas or other polluted gases. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0034] Figure 1 is the air filtration efficiency of the nanofiber air filtration membrane obtained in Comparative Example 1 of the present application;

[0035] Figure 2 is the air filtration efficiency of the nanofiber air filtration membrane obtained in Example 1 of the present application;

[0036] Figure 3 This is a scanning electron microscope image of the nanofiber air filtration membrane obtained in Comparative Example 1 of the present application;

[0037] Figure 4 is a scanning electron microscope image of the nanofiber air filtration membrane obtained in Example 1 of the present application;

[0038] Figure 5 This is a water contact angle diagram of the nanofiber air filtration membrane obtained in Comparative Example 1 of the present application;

[0039] Figure 6 This is a water contact angle diagram of the nanofiber air filtration membrane obtained in Example 1 of the present application;

[0040] Figure 7 is the infrared spectra of the nanofiber air filtration membranes obtained in Example 1 and Comparative Example 1 of the present application;

[0041] Figure 8 The effect of changing the concentration of melamine on the PM2.5 in the modified polyethanol nanofiber air filter membrane in Example 1 of this application is 0.3 Result diagram of the impact on filtration performance;

[0042] Fig. 9 The effect of changing the concentration of melamine on the PM2.5 in the modified polyethanol nanofiber air filter membrane in Example 1 of this application is 1.0 Result diagram of the impact on filtration performance;

[0043] Fig.10 The effect of changing the concentration of melamine on the PM2.5 in the modified polyethanol nanofiber air filter membrane in Example 1 of this application is 2.5 Result diagram of the impact on filtration performance;

[0044] Fig.11 is a scanning electron microscope image of the nanofiber air filter membrane obtained in Example 2;

[0045] Fig.12 is an air filtration efficiency diagram of the nanofiber air filtration membrane obtained in Example 2;

[0046] Fig.13 is a scanning electron microscope image of the nanofiber air filter membrane obtained in Example 3;

[0047] Fig.14 This is a graph of the air filtration efficiency of the nanofiber air filtration membrane prepared in Example 3. DETAILED DESCRIPTION

[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0049] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0050] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0051] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0052] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0053] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also indicate the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as µg, mg, g, kg, etc.

[0054] The term "PET" is the abbreviation of "Polyethylene terephthalate", which means polyethylene terephthalate; the term "PU" is the abbreviation of "polyurethane", which means polyurethane material and is the abbreviation of polyurethane.

[0055] Example 1

[0056] In this embodiment, the solvent is water, and the masses of polyvinyl alcohol: melamine: aluminum oxide nanoparticles are 1 g, 10 g, 0.5 g and 0.01 g respectively.

[0057] The preparation steps of nanofiber air filter membrane are as follows:

[0058] 1) Dissolve polyvinyl alcohol in water to form a viscous liquid A1 with a concentration of 10 g / mL;

[0059] 2) Melamine was dissolved in water to form a uniform solution, and then an appropriate amount of hydrochloric acid was added for cross-linking, with a pH value of 5. After heating at 80°C and stirring for 36 hours, a viscous liquid B1 was formed with a concentration of 12 g / mL;

[0060] 3) adding aluminum oxide nanoparticles to the remaining water and stirring at room temperature for 6 hours under ultrasonic wave to form a suspension solution C1;

[0061] 4) adding solution C1 dropwise into viscous liquid B1 and mechanically stirring at room temperature for 36 hours to form viscous liquid D1;

[0062] 5) Add viscous liquid D1 to viscous liquid A1 and stir at room temperature for 2 hours to form a mixed solution E1;

[0063] 6) The mixed solution E1 was electrospun (voltage: 18 kV, collection distance: 25 cm, liquid feeding speed: 0.1 mL / h) to obtain a primary nanofiber air filter membrane;

[0064] 7) The nascent nanofiber air filtration membrane was treated at 120° C. for 2 h to obtain a nanofiber air filtration membrane (modified polyvinyl alcohol nanofiber membrane).

[0065] Example 2

[0066] In this embodiment, the solvent is water, and the masses of polyethylene glycol: water: melamine: zirconium oxide nanoparticles are 1 g, 9 g, 0.2 g and 0.005 g respectively.

[0067] The preparation steps of nanofiber air filter membrane are as follows:

[0068] 1) Dissolve polyethylene glycol in some water to form a viscous liquid A2 with a concentration of 20 g / mL;

[0069] 2) Melamine was dissolved in part of the water to form a uniform solution, and then an appropriate amount of nitric acid was added for cross-linking, with a pH of 5. After heating at 88°C and stirring for 34 hours, a viscous liquid B2 was formed with a concentration of 20 g / mL.

[0070] 3) adding zirconium oxide nanoparticles to the remaining water and stirring at room temperature for 6 hours under ultrasonic wave to form a suspension solution C2;

[0071] 4) adding solution C2 dropwise into viscous liquid B2 and mechanically stirring at room temperature for 36 hours to form viscous liquid D2;

[0072] 5) Add the viscous liquid D2 to the viscous liquid A2 and stir at room temperature for 2 hours to form a mixed solution E2;

[0073] 6) Taking the mixed solution E2 for electrospinning (voltage: 25 kV, collection distance: 50 cm, liquid feeding speed: 5 mL / h) to obtain a primary nanofiber air filtration membrane;

[0074] 7) Treating the nanofiber air filter membrane at 200° C. for 2 h to obtain the nanofiber air filter membrane.

[0075] Example 3

[0076] In this embodiment, the solvent is water, and the masses of polyvinyl alcohol: melamine: aluminum oxide nanoparticles are 1 g, 12 g, 0.4 g and 0.01 g respectively.

[0077] The preparation steps of nanofiber air filter membrane are as follows:

[0078] 1) Dissolve polyvinyl alcohol in water to form a viscous liquid A3 with a concentration of 5 g / mL;

[0079] 2) Melamine was dissolved in water to form a uniform solution, and then an appropriate amount of hydrochloric acid was added for cross-linking, with a pH value of 4.8. After heating to 78°C and stirring for 10 hours, a viscous liquid B3 was formed with a concentration of 30 g / mL;

[0080] 3) adding aluminum oxide nanoparticles into water and stirring at room temperature for 6 hours under ultrasonic wave to form a suspension solution C3;

[0081] 4) adding solution C3 dropwise into viscous liquid B3 and mechanically stirring at room temperature for 36 hours to form viscous liquid D3;

[0082] 5) Add the viscous liquid D3 to the viscous liquid A3 and stir at room temperature for 2 hours to form a mixed solution E3;

[0083] 6) Taking the mixed solution E3 for electrospinning (voltage: 5 kV, collection distance: 100 cm, liquid feeding speed: 50 mL / h) to obtain a primary nanofiber air filtration membrane;

[0084] 7) treating the nascent nanofiber air filtration membrane at 80° C. for 3 h to obtain a nanofiber air filtration membrane.

[0085] Comparative Example 1

[0086] Compared with Example 1, the difference is that no nanoparticles are added, that is, the third step is omitted, and a polyvinyl alcohol nanofiber membrane is obtained.

[0087] 1. The fiber membranes obtained in Example 1 and Comparative Example 1 were subjected to air filtration test experiments. The simulated air composition used in both experiments was the same. The results are shown in FIG. Figure 1 and Figure 2 As shown, Figure 1 is the filtration curve of the fiber membrane in Comparative Example 1, Figure 2 is the filtration curve of the nanofiber air filtration membrane in Example 1. Figure 1 It can be seen that the filtration efficiency for PM1.0 is greater than 84%, and the filtration efficiency for PM2.5 is greater than 90%. Figure 2 It can be seen that the filtration efficiency for PM1.0 is greater than 99.%, and the filtration efficiency for PM2.5 is 100%.

[0088] 2. The morphology of the fiber membranes obtained in Example 1 and Comparative Example 1 was tested. The results are as follows: Figure 3 and Figure 4 The average fineness of the fiber membrane in Comparative Example 1 is 346 nanometers; the average fineness of the nanofiber air filtration membrane in Example 1 is 224 nanometers.

[0089] 3. The hydrophilicity of the fiber membranes obtained in Example 1 and Comparative Example 1 was tested, and the results are as follows: Figure 5 and Figure 6 The water contact angle of the fiber membrane in Comparative Example 1 is 0°; the water contact angle of the nanofiber air filter membrane in Example 1 is 110.478°.

[0090] 4 The structure of the fiber membrane obtained in Example 1 and Comparative Example 1 is tested, and the results are as follows: Figure 7 As shown in Figure 7, the hydroxyl stretching vibration peak of the nanofiber air filtration membrane obtained in Example 1 is significantly weakened compared with the fiber membrane in Comparative Example 1.

[0091] 5. The effect of melamine concentration on the air filtration performance of the nanofiber air filtration membrane was studied. The amount of melamine added in Example 1 was changed to 0.22g, 0.34g, 0.46g, and 0.58g respectively. The other steps were exactly the same as in Example 1. The test results are as follows: Figure 8-10 shown.

[0092] Depend on Figure 8-10 It can be seen that melamine concentration has a greater impact on the filtration of small air particles, where small air particles mainly refer to particles in the air with a particle size less than or equal to 1.0um. The smaller the diameter of small air particles, the greater the impact.

[0093] The electron microscope image of the nanofiber air filter membrane prepared in Example 2 is as follows: Fig.11 As shown; the test diagram of air filtration is as follows Fig.12 As shown by Fig.11 It can be seen that the nanofiber air filtration membrane was successfully prepared in Example 2. Fig.12 It can be seen that the air filtration performance is good.

[0094] The electron microscope image of the nanofiber air filter membrane prepared in Example 3 is as follows: Fig.13 As shown; the test diagram of air filtration is as follows Fig.14 As shown by Fig.13 It can be seen that the nanofiber air filtration membrane was successfully prepared in Example 3. Fig.14 It can be seen that the air filtration performance is good.

[0095] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A nanofiber air filter membrane, characterized in that: Made from the following ingredients: Hydrolyze polymers, organic matter, nanoparticles, solvents and acidic solutions that can ionize hydroxyl groups; The mass ratio of the polymer that can ionize hydroxyl groups by hydrolysis, the solvent, the organic matter and the nanoparticles is 0.8-1.2:8-12:0.2-0.6:0.004-0.012, and the pH value of the acidic solution and the solvent after mixing is 4.5-6; Wherein, the organic matter is melamine, silicon tetrachloride or divinylbenzene; The nanoparticles are at least one of aluminum oxide, zirconium dioxide and silicon dioxide; The solvent is water; The polymer capable of ionizing hydroxyl groups by hydrolysis is at least one of polyvinyl alcohol, polyacrylamide, polyacrylic acid, polyvinyl pyrrolidone, polymaleic anhydride and polyethylene glycol.

2. The nanofiber air filtration membrane according to claim 1, characterized in that: The particle size of the nanoparticles is 10-500 nm.

3. The nanofiber air filtration membrane according to claim 1, characterized in that: The mass ratio of the polymer that can ionize hydroxyl groups by hydrolysis, the solvent, the organic matter and the nanoparticles is 1:10:0.5:0.01, and the pH value of the acidic solution and the solvent after mixing is 5.

4. A method for preparing the nanofiber air filtration membrane according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The polymer capable of ionizing hydroxyl groups by hydrolysis is dissolved in a part of the solvent to form a viscous liquid A, wherein the concentration of the viscous liquid A is 5-20 g / mL; Melamine, silicon tetrachloride or divinylbenzene are dissolved in part of water to form a uniform solution, and then an acidic liquid is added for cross-linking to form a viscous liquid B, wherein the concentration of the viscous liquid B is 10-30 g / mL; adding the nanoparticles into the remaining solvent and dispersing them to form a suspension solution C; The suspension solution C is added dropwise to the viscous liquid B, and the mixture is stirred at room temperature to obtain a viscous liquid D; Viscous liquid D is added to viscous liquid A and stirred to form a mixed solution E; The mixed solution E is spun to obtain a primary nanofiber air filter membrane; The newly formed nanofiber air filter membrane is dried and dehydrated to obtain the nanofiber air filter membrane.

5. The method for preparing the nanofiber air filter membrane according to claim 4, characterized in that: The temperature for adding the acidic liquid for cross-linking is 70-90° C. and the time is 30-48 hours.

6. The method for preparing the nanofiber air filtration membrane according to claim 4, characterized in that: The spinning adopts an electrostatic spinning method or an airflow spinning method. The spinning conditions of the electrostatic spinning are: a voltage of 10-25 kV, a collection distance of 5-100 cm, a liquid feed speed of 0.1-100 mL / h, and an airflow speed of 0.1-50 m / s; the conditions of the airflow spinning method are: a collection distance of 5-100 cm, a liquid feed speed of 0.1-100 mL / h, and an airflow speed of 0.1-50 m / s.

7. The method for preparing the nanofiber air filtration membrane according to claim 6, characterized in that: The collection distance is 5~50 cm, the liquid inlet rate is 0.1~10 mL / h, and the air flow rate is 0.1~20m / s.

8. The method for preparing the nanofiber air filtration membrane according to claim 4, characterized in that: The acidic liquid includes at least one of hydrochloric acid, nitric acid and acetic acid.

9. Use of the nanofiber air filter membrane according to any one of claims 1 to 3 or the filter membrane obtained by the preparation method according to any one of claims 4 to 8 in gas purification, characterized in that: The gas includes air, polluted gas or industrial exhaust gas.